The Influence of Consumer Behavior on Purchasing Decisions for Mobile Legends Online Game Items for STIE Pembangunan Tanjungpinang Students - Satriadi Satriadi; Eko Putra; Mardahleni Mardahleni; Fikri Zulhendra (Journal of International Accounting, Taxation and Information Systems, 2024)
The purpose of this study is to determine the influence of consumer behavior on the decision to purchase Mobile Legends game items for STIE Pembangunan Tanjungpinang students. The method used in this research is a quantitative method. The object of this research is STIE Pembangunan Tanjungpinang students. Samples were taken as many as 346 respondents using purposive sampling technique. The data analysis technique used is data quality test, classic assumption test, simple linear regression test and hypothesis testing with the help of the SPSS 24 program. The results of this study indicate that the data are valid, reliable and normal. The heteroscedasticity test shows no heteroscedasticity. Based on the hypothesis test, the t test shows that the consumer behavior variable (X) has a significant effect on purchasing decisions (Y). In the coefficient of determination test, consumer behavior has a significant effect on the decision to purchase Mobile Legends game items for STIE Pembangunan Tanjungpinang students by 98.5%. The conclusion in this study shows that consumer behavior has a significant effect on the decision to purchase Mobile Legends game items for STIE Pembangunan Tanjungpinang students. This can be seen in the t value of the consumer behavior variable which is 2.041 and t table is 1.996 so that t value> t table (2.041> 1.996) and the significance value is less than 0.05, namely 0.042 (0.042 <0.05)